\(4x\left(5x-1\right)+10x=2\Leftrightarrow4x\left(5x-1\right)+10x-2=0\)
\(\Leftrightarrow4x\left(5x-1\right)+2\left(5x-1\right)=0\Leftrightarrow\left(4x+2\right)\left(5x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}4x+2=0\\5x-1=0\end{matrix}\right.\) \(\Leftrightarrow\left[{}\begin{matrix}4x=-2\\5x=1\end{matrix}\right.\) \(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{-1}{2}\\x=\dfrac{1}{5}\end{matrix}\right.\) vậy \(x=\dfrac{-1}{2};x=\dfrac{1}{5}\)
4x(5x-1)+10x=2
<=> 20x-4x+10x = 2
<=> 26x = 2
<=> x = \(\dfrac{1}{13}\)
\(4x\left(5x-1\right)+10x=2\)
\(\Leftrightarrow20x-4+10x=2\)
\(\Leftrightarrow20x+10x=2+4\)
\(\Leftrightarrow30x=6\)
\(\Leftrightarrow x=\dfrac{1}{5}\)
Vậy .....